Dental Pulp Stem Cells: An Attractive Alternative for Cell Therapy in Ischemic Stroke - Lan, Xiaoyan (Front Neurol, 2019)
Ischemic stroke is a major cause of disability and mortality worldwide, but effective restorative treatments are very limited at present. Regenerative medicine research revealed that stem cells are promising therapeutic options. Dental pulp stem cells (DPSCs) are autologously applicable cells that origin from the neural crest and exhibit neuro-ectodermal features next to multilineage differentiation potentials. DPSCs are of increasing interest since they are relatively easy to obtain, exhibit a strong proliferation ability, and can be cryopreserved for a long time without losing their multi-directional differentiation capacity. Besides, use of DPSCs can avoid fundamental problems such as immune rejection, ethical controversy, and teratogenicity. Therefore, DPSCs provide a tempting prospect for stroke treatment.